Pemberdayaan Kader dalam Upaya Deteksi Dini Ibu Hamil Resiko Tinggi di Wilayah Kerja Puskesmas Simpang Sungai Duren - Muthia Mutmainnah; Putri Irwanti Sari; Yulia Indah Permata Sari (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Early pregnancy detection is important to identify pregnant women who have risk factors and obstetric complications. The aim of the service is to provide information and increase health cadres' knowledge about high-risk pregnancies. Activities are carried out using lecture and direct practice methods. Implementation of service in the Community Health Center Hall. The activity participants were community health center cadres totaling 36 participants. The activity went smoothly and the participants looked enthusiastic. The results of the service show that the age characteristics of the early adult category cadres are 18 (50%). After the evaluation, most of the cadres' knowledge increased regarding early detection of high-risk pregnancies compared to before the education was provided. After carrying out this community service, it is hoped that cadres can play an active role in carrying out early detection supported by health workers in an effort to prevent obstetric complications.